Islamic Finance Practices in Micro, Small, and Medium Enterprises in Indonesia: A Systematic Literature Review - Selamet Hartanto; Tri Suparyanto; Azwar (Program Studi Ilmu Agama Islam Program Magister, Universitas Islam Indonesia, 2023)
This study analyzes Islamic finance practices in micro, small, and medium enterprises (MSMEs) in Indonesia from an Islamic economics perspective. This study employed a systematic literature review method following the Preferred Reporting Items for Systematic Reviews and Meta-Analyses (PRISMA). The main data source was written material that analyzed the impact of Islamic finance practices on MSMEs in Indonesia. The findings demonstrate that Islamic finance practices positively influence the growth of MSMEs in Indonesia. This study indicates that Islamic finance practices have substantial potential for enhancing the well-being of MSMEs in the country. Noteworthy growth factors for MSMEs encompass Islamic business and economic ethics, innovation, and ethical and moral considerations. Islamic finance practices are a promising option for Indonesian MSMEs to enhance their business growth. Therefore, adopting Islamic finance practices can contribute to improving business performance and fostering MSMEs' growth. Future research may involve empirical studies to gain a more comprehensive understanding of Islamic finance practices in Indonesian MSMEs.